2013
DOI: 10.14326/abe.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Assessment of a Laparoscopic Stapler

Abstract: The laparoscopic stapler is a surgical instrument that automatically creates visceral anastomosis. Although the laparoscopic stapler is widely used, objective ergonomic assessments are lacking. The purpose of this study was to quantitatively assess the force and muscle activities involved during the use of a laparoscopic stapler. The mechanical force needed to create anastomosis in a cattle colon was measured using a tensile tester. Three different loads (150 N, 200 N, and 250 N) were applied individually to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Twenty-nine non-randomized studies were included in this review [ 19 , 21 30 , 32 34 , 50 , 52 , 54 , 55 , 57 , 59 , 61 68 , 70 ]. For this study design, the MMAT considers appropriateness of measurement and analysis methods, administration of or exposure to intervention, completeness of results, accounting for confounders, and generalizability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-nine non-randomized studies were included in this review [ 19 , 21 30 , 32 34 , 50 , 52 , 54 , 55 , 57 , 59 , 61 68 , 70 ]. For this study design, the MMAT considers appropriateness of measurement and analysis methods, administration of or exposure to intervention, completeness of results, accounting for confounders, and generalizability.…”
Section: Resultsmentioning
confidence: 99%
“…For this study design, the MMAT considers appropriateness of measurement and analysis methods, administration of or exposure to intervention, completeness of results, accounting for confounders, and generalizability. Data collection methods included physical measurements [ 50 , 55 , 59 , 61 , 63 67 ], EMG [ 52 , 55 , 59 , 68 ], dynamometry [ 59 , 61 , 63 , 70 ], and performance metrics [ 19 , 21 30 , 32 34 , 55 ]. All these measurement methods appeared to be relevant and appropriately controlled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, left‐handed surgeons in our study also had a significant increase in difficulty with the endoscopic stapler, confirming the ergonomics of this specific instrument needs improvement to fully satisfy a wider population of veterinary surgeons. The use of endoscopic stapling equipment requires not only the force to close the jaws, which can be substantially higher than grip strength in surgeons with small glove size, 19 but also necessitates manipulation to cut the tissue and to articulate or position the blade. An improper handle‐to‐hand‐size relationship for surgeons with smaller glove sizes is likely responsible for the increased difficulty associated with performing maneuvers designed to be executed with a single hand.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive force required to operate TLS tools is well documented. Kasai et al [ 19 ] demonstrated that 250 N was required to properly fire an anastomotic stapler. This level of force is sometimes unattainable for female surgeons due to their strength and grip diameter.…”
Section: Introductionmentioning
confidence: 99%